2018
DOI: 10.1111/cgf.13344
|View full text |Cite
|
Sign up to set email alerts
|

PointProNets: Consolidation of Point Clouds with Convolutional Neural Networks

Abstract: With the widespread use of 3D acquisition devices, there is an increasing need of consolidating captured noisy and sparse point cloud data for accurate representation of the underlying structures. There are numerous algorithms that rely on a variety of assumptions such as local smoothness to tackle this ill‐posed problem. However, such priors lead to loss of important features and geometric detail. Instead, we propose a novel data‐driven approach for point cloud consolidation via a convolutional neural network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…Moreover, we found that a straightforward implementation might not converge, while with the proper loss and with an inflation term, the network can both stabilize and achieve higher accuracy. [RÖPG18]. The two plots on the left are evaluated on our test set without outliers, the two following plots compare the outlier removal performance using the f1 and the f2 scores and the right-most plot shows the denoising performance after outlier removal.…”
Section: Lossmentioning
confidence: 99%
“…Moreover, we found that a straightforward implementation might not converge, while with the proper loss and with an inflation term, the network can both stabilize and achieve higher accuracy. [RÖPG18]. The two plots on the left are evaluated on our test set without outliers, the two following plots compare the outlier removal performance using the f1 and the f2 scores and the right-most plot shows the denoising performance after outlier removal.…”
Section: Lossmentioning
confidence: 99%
“…In addition to denoising networks, some other neural network architectures involve point cloud consolidation, which includes denoising but is often only applicable to trivial noise. PointProNet [27] projects patches in the point cloud into 2D height maps and leverages a 2D CNN to denoise and upsample them. EC-Net [37] and 3PU [36] mainly focus on upsampling, and have shown to be robust against trivial noise.…”
Section: Deep-learning Based Point Cloud Denoisingmentioning
confidence: 99%
“…A key component of our method is a differentiable module to generate depth images from the points, which can be inserted into any neural network architecture. We took [21] where the authors create depth field images by projecting the points onto an image plane. However, their method is designed to handle local patches of points, where the geometry is well represented with a height field without occluded parts.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, we want to estimate the K camera-pose matrices which represent 3D rotations to transform the point cloud in order to perform an orthogonal projection. Inspired by [21], we start from the recent method PointNet [17], which proposes a network architecture that allows for processing unordered 3D point sets, like our input. The prediction of the views should respect crucial properties such as invariance to permutations of the input data and invariance under transformations.…”
Section: View Predictionmentioning
confidence: 99%
See 1 more Smart Citation